PENGARUH STRATEGI PENYEIMBANGAN ANTARA AKTIVITAS PEKERJAAN DAN KELUARGA TERHADAP KESEJAHTERAAN KELUARGA SUBJEKTIF PADA PEREMPUAN BEKERJA DI BOGOR: Analisis Structural Equation Modelling - Puspitawati, Herien (Jurnal Ilmu Keluarga dan Konsumen, 2009)
The main purpose of this research was to know the effect of working women’s strategy in balancing between work and family towards the subjective family well-being. The respondents were working women who work in full-time and had a husband and a child or children. This was a cross sectional study which was performed among 50 working women in Bogor in March 2005. Almost all respondents were experienced in working because they have been working for about 15 years. The families of all respondents were in middleupper class families. The results showed that most of respondents performed the strategy of balancing between work and family activities. The overall subjective family well-being was measured by respondents’ satisfaction towards their resources and conditions of physically, economically, socially, and psychologically. It was found that the strategic of women that tend to prioritize the family purposes had positive effect to the subjective family well-being.